Analysis of Trust Models in Public Key Infrastructure: A Systematic Literature Review of Interoperability Challenges - R.Radzali; Azni Hazlizan Ab Halim; Farida Hazwani Mohd Ridzuan; Nur Hafiza Zakaria; Tasnuva Ali (Universiti Sains Islam Malaysia, 2025)
Indexed